STRATEGI KYAI DALAM MENINGKATKAN KUALITAS MENGAJAR ASATIDZ DI PONDOK PESANTREN ANNIDA KEC. SELOMERTO WONOSOBO 2025 - Fikri Husni Fauzan; Ngarifin Shidiq; Mukromin Mukromin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to examine the role of the kyai in improving the teaching quality of asatidz at Pondok Pesantren Annida. The focus of the research includes the kyai’s leadership abilities in guiding educators, the strategies implemented to enhance teaching professionalism, as well as the supporting and inhibiting factors that influence the effectiveness of these strategies. The study employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The research subjects consist of the pesantren leader, caregivers, senior teachers, and newly appointed teachers. Data analysis was carried out through the stages of data collection, reduction, and conclusion drawing. The findings reveal that Kyai Rahmat Salim possesses strong managerial and communication skills in fostering the asatidz, enabling the creation of a more effective learning environment. The strategies applied to improve teaching quality include competency development, the provision of learning facilities, personal approach, continuous evaluation and monitoring, and amaliyah tadris training for final grade students as future educators. Major supporting factors include the active leadership of the kyai, routine pesantren activities, and the commitment of the asatidz. However, several challenges were also identified, such as schedule conflicts between teaching and external work, limited motivation among some teachers to develop their teaching skills, and decreasing enthusiasm in professional improvement.